Synergism between corrosion and wear on CoCrMo−Al2O3 biocomposites in a physiological solution - Ribeiro, A. M.; Alves, A. C.; Rocha, L. A. [UNESP]; Silva, F. S.; Toptan, F. (Elsevier, 2015)
The use of metal matrix composite structures in biomedical implants can be a solution for decreasing the amount of degradation products. Thus, the present work aims to investigate the synergism between corrosion and wear on CoCrMo matrix 10% (vol) Al2O3 particle reinforced composites in phosphate buffer solution (PBS) at body temperature. Corrosion behavior was investigated by electrochemical impedance spectroscopy and potentiodynamic polarization. Tribocorrosion tests were performed under open circuit potential, as well as under cathodic and anodic potentiostatic conditions using a reciprocating ball-on-plate tribometer. Results suggest that the addition of Al2O3 particles did not create a significant effect on corrosion behavior of CoCrMo alloy, however, it increased the wear resistance and decreased the corrosion kinetics when sliding in PBS solution.
Keywords: Corrosive degradation; Metal matrix composite; Synergism of wear and corrosion; Tribochemistry